Route Map of Privacy Preservation to IOT - Pravin N. Kathavate, Mr; J. Amudhavel, Dr (International Journal of Engineering and Technology, 2018)
Data anonymization is the main feature of privacy preservation, and it assists in eradicating the privacy hazard in data preparation in various applications including IoT. Pseudonymity and Anonymization are two significant security factors that were adopted when sensitive data are shared.Â  In medical field, data is usually distributed horizontally with diverse regions carrying a similar set of characteristics for various anonymization techniques. Accordingly, this paper intends to formulate a review on privacy preservation in IoT. Here, the literature analyses on diverse techniques associated with data hiding, data preservation and data anonymization along with data restoration properties. It reviews 60 research papers and states the significant analysis. Initially, the analysis depicts the chronological review of the overall contribution of different types of anonymization protocols in diverse applications. Subsequently, the analysis also focuses on various features such as applications, measures, key generation and data preservation in healthcare, etc. Furthermore, this paper provides the detailed performance study regarding data hiding and restoration process in each contribution. Finally, it extends the various research issues which can be useful for the researchers to accomplish further research on data preservation in IoT.Â